SOFCs with Sc-doped zirconia electrolyte and Co-containing perovskite cathodes - Jung, Hwa Young; Hong, Kug-Sun; Jung, Hun-Gi; Kim, Hyoungchul; Kim, Hae-Ryoung; Son, Ji-Won; Kim, Joosun; Lee, Hae-Weon; Lee, Jong-Ho (ELECTROCHEMICAL SOC INC, 2007)
Recently, much attention has been directed toward the study of Sc-doped zirconia electrolyte for intermediate-temperature SOFCs (IT-SOFCs) due to its fairly good ionic conductivity compared with conventional Y-doped zirconia, which can reduce the internal ohmic loss of the cell. For improving unit cell performance, another important point to be considered is the selection of appropriate electrode materials to reduce the polarization loss at the electrode. In this study, we fabricated anode-supported SOFCs with a 1 mol % CeO2 codoped 10 mol % Sc2O3-ZrO2 (CeSSZ) electrolyte. Various kinds of cathode materials such as La-Sr-Mn-O, La-Sr-Co-O (LSCo), La-Sr-Co-Fe-O, and Sm-Sr-Co-O (SSCo) have been applied in order to identify the most suitable cathode material for Sc-doped zirconia. We evaluated the power-generating characteristics of 5x5 cm scaled unit cells as well as the cathode polarization effect via a dc current-voltage measurement, a dc current interruption method, and ac impedance spectroscopy. We also thoroughly investigated the interfacial reaction between the electrolyte and the cathode in order to identify appropriate heat-treatment conditions for each candidate cathode material on the CeSSZ electrolyte. According to the investigation, unit cells with a SSCo and LSCo cathode showed superior power density of 1.13 and 1.33 W/cm(2), respectively, at 700 degrees C and fairly stable cell performance without any serious interfacial reaction. (c) 2007 The Electrochemical Society.
Keywords: OXIDE FUEL-CELLS; SM0.5SR0.5COO3 CATHODES; PERFORMANCE; FILM